Characterizing Features of Human Circulating B Cells Carrying CLL-Like Stereotyped Immunoglobulin Rearrangements - Bagnara, Davide; Colombo, Monica; Reverberi, Daniele; Matis, Serena; Massara, Rosanna; Cardente, Niccolò; Ubezio, Gianluca; Agostini, Vanessa; Agnelli, Luca; Neri, Antonino; Cardillo, Martina; Vergani, Stefano; et al. (Frontiers in Oncology, 2022)
Chronic Lymphocytic Leukemia (CLL) is characterized by the accumulation of monoclonal CD5+ B cells with low surface Immunoglobulins (IG). About 40% of CLL clones utilize quasi-identical B cell receptors, defined as stereotyped BCR. CLL-like stereotyped-IG rearrangements are present in normal B cells as a part of the public IG repertoire. In this study, we collected details on the representation and features of CLL-like stereotyped-IG in the IGH repertoire of B-cell subpopulations purified from the peripheral blood of 9 healthy donors. The B-cell subpopulations were also fractioned according to the expression of surface CD5 molecules and IG light chain, IG𝜅 and IG𝝀. IG rearrangements, obtained by high throughput sequencing, were scanned for the presence of CLL-like stereotyped-IG. CLL-like stereotyped-IG did not accumulate preferentially in the CD5+ B cells, nor in specific B-cell subpopulation or the CD5+ cell fraction thereof and their distribution was not restricted to a single IG light chain type. CLL-like stereotyped-IG shared with the corresponding CLL stereotype rearrangements the IGHV mutational status. Instead, for other features such as IGHV genes and frequency, CLL stereotyped-IGs presented a CLL-like subset specific behavior which could, or could not, be consistent with CLL stereotyped-IGs. Therefore, as opposed to the immuno-phenotype, the features of the CLL stereotyped-IG repertoire suggest a CLL stereotyped subset-specific ontogeny. Overall, these findings suggest that the immune-genotype can provide essential details in tracking and defining the CLL cell of origin.